Conservation Strategy and Ecotourism Impact Counseling Mangrove on The Coastal Mangrove Beach of Nipah Village District Serdang Various Sumatera North - Muhammad Iqbal; Kelas A Geografi Stambuk 2023 (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Sei Naga Lawan is a coastal village that has natural tourism potential and is included in an ecotourism conservation area that can revive the economy, especially on the mangroves coast of Kampung Nipah, Serdang Bedagai Regency, North Sumatra. To increase the participation of the Kampung Nipah Village community, the researchers initiated a mini community service program that is directly related to the empowerment of natural tourism potential in Sei Naga Lawan Village, especially the development of the beach area in Village Nipa palm. In connection with the above, researchers conducted socialization and strategies for conservation and management of mangrove forest using lecture and discussion methods followed by mangrove planting activities. The results of the activity show that the implementation of the Community Service Program in Kampung Nipah, Sei Naga Lawan District has been successfully carried out well. This can be seen from the enthusiasm of community members during lectures and discussions. During the seedling planting stage, they also worked together to plant according to what the service team directed. It is hoped that this service can provide knowledge and provide understanding and skills to the local community that Kampung Nipah, Sei Naga Lawan District has an important role as an economist buffer in the future.